Al-Biruni is a sociologist and anthropologist - Mohammed, Abdulrazzaq Jadou (Al-Adab Journal, 2015)
Bearoni based in social studies and anthropology on solid scientific research methods consisted of note and participant observation through his travels and field his travels. And use of reason in the elicitation, analysis and conclusion as well as the approach of doubt and rely on quantitative measurement methods. The adopted approach and comparative lack of tradition, transport and followers adoption. 2- The study of the Indian community were theoretical and practical study, as compare communities and endured these communities from the teachings and rituals. and discovered that there are similarities and differences between these communities.3- He Link between linguistics and literature meeting and stressed that the values ​​and etiquette and language dependent and influenced by its environment from natural climate and plant economic and community resources habits.4- He think there is a link between religion and philosophy, and politics. And that the source of the laws and regulations is a religion.5- Compare the buildings between social communities and noted that the reasons for the differences between the building and the building is due to the nature of the profession and the density of population and geographical distribution of the population.6- That the social relations as seen by the Peronist between individuals and groups but are positive relationships based on closeness and love, and there is a negative relationship based on differences and rivalry.7- He think that the profession is the basis of society is divided into classes, there is a religious class and there warrior class and the class then there are agricultural business class